Supplier selection in institutions of residential care - Ivana Marjanović; Loukas Tsironis; Jason Papathanasiou (Economic Themes, 2025)
The selection of suppliers in public procurement significantly impacts economic efficiency and social wellbeing, particularly within residential care institutions responsible for vulnerable populations. Despite the strategic importance of procurement decisions, limited research has addressed criteria weighting in the specific context of residential care. This study bridges this gap by applying the group Analytic Hierarchy Process (group AHP) to determine the weights of selected procurement criteria in residential care institutions in Serbia. Results indicate that price remains the dominant factor, though sustainability considerations are increasingly influential, aligning procurement practices with broader regulatory and policy goals. Moderately weighted criteria emphasize the importance of contractual clarity and fairness, while delivery time is found to be of comparatively lower priority. The application of group AHP demonstrates strong consistency among expert judgments, highlighting its effectiveness in enhancing transparency and reducing potential biases or corruption. The findings underscore the necessity of embedding scientifically grounded multi-criteria approaches into public procurement frameworks and suggest comprehensive training for procurement professionals to facilitate informed, sustainable, and socially responsible procurement decisions.
Keywords: C44; D81; H57; 330; Public procurement; Residential care institutions; Supplier selection; Criteria weighting; Group Analytic Hierarchy Process; Multi-criteria decision-making